Analisis Praktik Riba dalam Layanan Pinjaman Uang berbasis Fintech Lending Aplikasi Adapundi - Salim, Zainab; Muhammad Muchlis, Madian (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2024)
Lately, a wide variety of fintech lending-based loan offers (online loans) through applications can be found on all platforms. Many people are interested in using the service because of its easy requirements, large limits, long tenors, and fast disbursement processes. However, behind the attractive offer, there are several adverse effects including interest rates that are contrary to the principles of muamalah Islam. This study aims to describe the mechanism of fintech lending-based lending services in the Adapundi application and analyze the elements of riba practices in it based on Sharia economic law. This type of research is descriptive research using a qualitative approach. The research method used in this study is library research. The source of data in this study is the fintech lending application (online loans) Adapundi and its official website. The results of this study indicate that: (1) fintech-based loans lending is considered a quick and easy financial solution, but in its operation, there is an interest system that is prohibited in Islam. (2) there are two types of riba in the practice of lending money in the application of Adapundi, namely riba qardh and riba jahiliyah. The addition of the principal loan amount of 0.03% to 0.3% per day which is riba qardh and late penalties (between 1-7 days) which will be charged interest of 1.2% per day from the principal is riba jahiliyah.